Electrophoretic Deposition (EPD) of Multi-Walled Carbon Nanotubes (Mwcnts) Onto Carbon Fiber (CF) Fabric - Ervina, J; Hamdan, S; Rahman, MR (International Journal of Integrated Engineering, 2023)
The Fiber Reinforced Polymer Composite (FRPC) has been widely employed in structural applications. However, adding nanoparticles such as multi-walled carbon nanotubes (MWCNTs) can be used to improve the composites' mechanical properties substantially. The purpose of this study is to investigate the stability of MWCNTs in distilled water (DW) and dimethylformamide (DMF). Electrophoretic deposition (EPD) was chosen as the method for depositing MWCNTs onto carbon fiber (CF) fabric because of the advantages of simple equipment and inexpensive cost. Thus, the effect of voltage and deposition time were examined to attain the ideal condition for the EPD of MWCNTs onto CF fabric. The stability of dispersed MWCNTs in various dispersing mediums was explored as the importance of the MWCNTs to remain stable in the medium is essential to achieve homogeneous deposition. The UV-Vis and colloidal stability test revealed that MWCNTs dispersed in DMF have greater stability than DW. Scanning Electrode Microscopy (SEM) images exhibited that 10 minutes and a 20 V voltage were the optimal conditions for the deposition of MWCNTs onto CF fabric.